Factors associated with difficulty in crossing the culprit lesion of acute myocardial infarction - Shun Ishibashi (Nature Portfolio, 2021)
Abstract In percutaneous coronary intervention (PCI) to the culprit lesion of acute myocardial infarction (AMI), unsuccessful guidewire crossing causes immediate poor outcomes. It is important to determine the factors associated with unsuccessful guidewire crossing in AMI lesions. The purpose of this study was to find factors associated with difficulty in crossing the culprit lesion of AMI. We defined the difficult group when the guidewire used to cross the culprit lesion was a polymer jacket type guidewire or a stiff guidewire. We included 937 patients, and divided those into the non-difficult group (n = 876) and the difficult group (n = 61). Proximal reference diameter was significantly smaller in the difficult group than in the non-difficult group (p < 0.001), and degree of calcification was severer in the difficult group than in the non-difficult group (p < 0.001). In the multivariate stepwise logistic regression analysis, proximal reference diameter [odds ratio (OR) 0.313, 95% confidence interval (CI) 0.185–0.529, p < 0.001)], previous PCI (OR 3.065, 95% CI 1.612–5.830, p = 0.001), moderate-severe calcification (OR 4.322, 95% CI 2.354–7.935, p < 0.001), blunt type obstruction (OR 12.646, 95% CI 6.805–23.503, p < 0.001), and the presence of collateral to the culprit lesion (OR 2.110, 95% CI 1.145–3.888, p = 0.017) were significantly associated with difficulty in crossing the culprit lesion. In conclusion, previous PCI, calcification, blunt type obstruction, and the presence of collateral were associated with difficulty in crossing the culprit lesion, whereas proximal reference diameter was inversely associated with difficulty. Our study provides a reference to recognize the difficulty in crossing the culprit lesions of AMI for PCI operators, especially junior operators.